2019
DOI: 10.1111/1468-0106.12294
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of labour productivity: Comparison between developing and developed countries of Asia‐Pacific

Abstract: The current study investigates the trends in labour productivity of the major developing and developed economies of the Asia‐Pacific region and examines its determinants over the period 1980–2014. The study analyses capital deepening, human capital, technology, share of agriculture in GDP, financial development, institutional quality, inflation as well as macroeconomic variables as potential determinants of productivity, and identifies the differences in the impact of these factors on the productivity of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 44 publications
(74 reference statements)
3
26
0
8
Order By: Relevance
“…Real wages and high-tech were the two variables whose growth had a significant positive impact on productivity. These results are consistent with Zheng et al (2017) and Dua and Garg (2019), who also found that technological progress and human capital are important factors affecting productivity. For the Russian economy, Tumilevich (2019) demonstrated the role of the percentage of people with higher education in labor productivity.…”
Section: Spatial Analysis Of Labor Productivitysupporting
confidence: 91%
“…Real wages and high-tech were the two variables whose growth had a significant positive impact on productivity. These results are consistent with Zheng et al (2017) and Dua and Garg (2019), who also found that technological progress and human capital are important factors affecting productivity. For the Russian economy, Tumilevich (2019) demonstrated the role of the percentage of people with higher education in labor productivity.…”
Section: Spatial Analysis Of Labor Productivitysupporting
confidence: 91%
“…Gross wage could be an important element of the price, as well as for causality between gross wage and labour productivity. The problem of how to ensure the growth of labour productivity in tourism is especially relevant in developing economies (Dua & Garg, 2019;Silva & Guimarães, 2017;Stundziene & Saboniene, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, the study of factors affecting labour productivity is an important strand in economic literature. However, researchers have examined the differences in labour productivity between countries (Dua & Carg, 2019;Sakamoto, 2018;Tang & Wang, 2004) and sectoral contribution to labour productivity (Diewert, 2015;Roncolato & David, 2014) or have investigated the factors driving labour productivity in industries and companies (Kazaz et al, 2016;Muhammad et al, 2015;Tang, 2017;Ugur et al, 2016). Little attention has been given to the cross-regional differences in labour productivity within a country and their causes.…”
Section: Introductionmentioning
confidence: 99%